Development of Standalone Control Unit for Automotive Battery Management System - LINGAIAH JAYARAMU, MAITHRI (My University, 2020)
Conventional vehicles have made a great impact on climatic changes which in turn has made way for the electric vehicles in the market as they have zero emissions. Electric vehicles run on large number of batteries. Batteries are very sensitive to temperature variations and incorrect charging. The performance of the battery pack is dependent on various battery operating parameters that involve battery temperature, depth of discharge, charge and discharge rates. Monitoring the battery operating parameters is essential for safe and reliable operation of the cells, energy management system and maintenance of the battery. This thesis is about firmware development for battery monitoring, battery parameters measurement and battery state estimation using a Battery monitoring IC which is part of battery management system(BMS) in hybrid electric vehicles(HEV), plugin hybrid electric vehicles (PHEV) and battery electric vehicles(BEV). The customized hardware has a small ARM processor integrated into an FPGA which will establish connection with the Battery Monitoring IC and does the required configurations. Certain battery operating parameters are measured and monitored periodically by the Battery Monitoring IC and shunt based measurement system. Based on the calculated state of charge (SoC) further safety decisions are taken. This system is used in an integrated system, thus reduces data processing load for the main controller and also reduces the data traffic. As the system is modular, it is reusable in many other projects. The results of this thesis show that the firmware is capable of doing the battery monitoring, measure the battery operating parameters and perform battery state estimation. The tests implemented on the test bench were to verify the implementation, and to evaluate the battery state estimation algorithm.
Keywords: Battery management system; battery monitoring IC; measurement; battery operating parameters; SoC; safety; battery state estimation